Polypropylene pyrolysis and steam reforming over Fe-based catalyst supported on activated carbon for the production of hydrogen-rich syngas - Wang, Shuxiao; Sun, Yibo; Shan, Rui; Gu, Jing; Huhe, Taoli; Ling, Xiang; Yuan, Haoran; Chen, Yong (Carbon resources conversion, 2023)
[Display omitted] •A cheap and efficient Fe catalysts were synthesized with extremely simple method.•The as-synthesized catalysts show excellent selectivity for H2.•H2 yield is up to 38.73 mmol/gPP without water and 112.71 mmol/gPP with water.•Various forms (nanotubes and nanospheres) of graphite carbon were found.•Adding water can increases hydrogen production and prevents carbon buildup. The purpose of this study is to explore a method for the high-yield production of hydrogen by pyrolysis and steam reforming of polymer plastics. The developed Fe-based catalyst supported on activated carbon was applied to reactions with polypropylene for hydrogen production. The effects of iron loading (%) in the catalyst, the total catalyst amount, and the water content in the reaction atmosphere on the performance of hydrogen and gas production were investigated. Under the optimal conditions, the hydrogen yield without water added reached 38.73 mmol/gPP, and this yield was significantly improved by adding water into the reaction atmosphere. By optimizing the amount of water added, the hydrogen yield reached 112.71 mmol/gPP. The surface morphology and structural components of the fresh and used catalysts were characterized, and the morphology and quantity of carbon deposition on the catalyst were analysed. The catalytic stability of the 15Fe/AC catalyst was determined by repeating the test 10 times under the optimal reaction conditions. As the reaction time increased, the selectivity of the catalyst for hydrogen decreased and that for hydrocarbons increased. Moreover, the experimental method used in this study had excellent hydrogen production capacity. Thus, this study provided a novel method for the high-efficiency production of hydrogen by pyrolysis and steam reforming of polymer plastics.